1990
DOI: 10.1159/000125611
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Maturation Modifies the Catecholaminergic Control of Gonadotrophin Secretion and the Effect of Ovarian Hormones on Hypothalamic Neurotransmitters in Female Rats

Abstract: α-Methyl-p-tyrosine (α-MT), a competitive inhibitor of tyrosine hydroxylase, was used to block the synthesis of hypothalamic catecholamines in immature female rats of 14, 16 and 30 days of age and in castrated adults. The administration of α-MT (300 mg/kg body weight, free base) induced a significant decay in the hypothalamic content of norepinephrine (NE) and dopamine (DA) within the first 120 min. A second dose (150 mg/kg body weight), given 2 h after the first injection, did not further modify the low catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…We have recently demonstrated that the administra tion of sexual steroid hormones to female rats induces different changes in the hypothalamic content of amino acid before or after sexual maturation [24], and we have also postulated the maturation of new intemeuronal cir cuits during sexual maturation [25][26][27]. In order to in vestigate the possibility that sexual maturation might be accompanied by changes in the endogenous amino acid concentration in the hypothalamus and in the response of these neurons to stimulation or blockade of the NMDA receptor, the endogenous amino acid concen tration and the effect of pharmacological manipulation of the NMDA receptor on amino acid content in cer tain hypothalamic areas were measured in the present study.…”
mentioning
confidence: 91%
“…We have recently demonstrated that the administra tion of sexual steroid hormones to female rats induces different changes in the hypothalamic content of amino acid before or after sexual maturation [24], and we have also postulated the maturation of new intemeuronal cir cuits during sexual maturation [25][26][27]. In order to in vestigate the possibility that sexual maturation might be accompanied by changes in the endogenous amino acid concentration in the hypothalamus and in the response of these neurons to stimulation or blockade of the NMDA receptor, the endogenous amino acid concen tration and the effect of pharmacological manipulation of the NMDA receptor on amino acid content in cer tain hypothalamic areas were measured in the present study.…”
mentioning
confidence: 91%
“…It is probable that this change is connected with the modifications in the effect of catecholamines on gonadotropin secretion during sexual development previously described [12] as well as with an increase of rxr adrenoreceptors probably induced by an 229 increase of E2 activity during the maturational period [17]. Experiments are now in progress in order to clarify these points.…”
Section: Discussionmentioning
confidence: 80%
“…the decrease in the inhibitory action of opiates on LHRH neurons [22], the increase in the LHRH release effect of excitatory amino acids [23], etc. For instance, catecholamines have a predominantly inhibito ry effect on gonadotropin secretion in prepubertal rats while stimulating these pituitary hormones in peripuber tal and adult rats [12]. In a similar way, the possibility arises that the lack of effect of NE on PGE2 in prepubertal rats represents the existence, during sexual maturation, of a different qualitative relationship among the neurotrans mitters involved in gonadotropin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of serotonin and other catecholamines, and neurotransmitters such as GABA, on the hypothalamus change during pubertal development (Moguilevsky et al 1990(Moguilevsky et al , 1991. Distinct and well-defined populations of germ cells interact with Sertoli cells in a cyclic pattern.…”
Section: Discussionmentioning
confidence: 99%